KOLABORASI PERAWAT DAN DUKUNGAN KELUARGA DALAM PERAWATAN ANAK DENGAN ß-TALASEMIA MAJOR: STUDI KASUS - Hendrawati, Sri; Wahyuni, Dini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Thalassemia is one of the most common hemoglobinopathic disorders found worldwide. About 80% of thalassemia cases occur in low- or middle-income countries in the tropical belt, stretching from sub-Saharan Africa through the Mediterranean region and the Middle East to South and Southeast Asia, including Indonesia. Patients with thalassemia, especially in children, require routine and continuous treatment, which certainly requires support from nurses and families, especially parents as caregivers. With optimal support, it is expected to positively impact emotional well-being and the quality of life of patients and families. This study aimed to determine the collaboration of nurse support and family support that can be provided in providing care for children with β-thalassemia major. This research uses a case study approach in the field. Case studies are organized using the nursing process, including assessment, data analysis, intervention, implementation, evaluation, and nursing documentation. The subject of this case study is a patient with β-thalassemia major in one of the hospitals in Bandung. The case study was conducted for 11 days. A 9-year-old patient was admitted to the hospital with complaints of an enlarged abdomen and weight loss of 2 kg in the last two weeks. The patient has been diagnosed with β-thalassemia major since the age of 7, receives regular blood transfusions every two weeks, and takes oral iron chelation regularly. The family plays a vital role in managing β-thalassemia by adhering to all planned and recommended therapy regimens to overcome and prevent complications. Providing comprehensive bio-psychospiritual nursing interventions in collaboration with family support can improve a patient's quality of life with thalassemia because the welfare status of the family becomes the foundation of the child's quality of life. Nursing implications given to patients and families can reduce symptoms and support families with children suffering from thalassemia.